2023
DOI: 10.1186/s13102-023-00693-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of 10-week equipment-based pilates and diaphragmatic breathing exercise on heart rate variability and pulmonary function in young adult healthy women with normal BMI – a quasi-experimental study

Abstract: Background The positive effects of Pilates and slow-controlled breathing exercises on health are examined in different studies. The purpose of the study was to investigate the effects of 10-week equipment-based Pilates, slow-controlled breathing exercises, and a combination of both on heart rate variability (HRV), pulmonary function, and body composition (BC) in young adult healthy women with normal BMI. Methods Forty female participants were assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Respiratory physiotherapy is a set of techniques intended to prevent, treat, and stabilize cardiorespiratory disorders. 13 It is a helpful approach to preserving and enhancing functional capacity, quality of life, and post-treatment sequelae following breast cancer care. 14 , 15 However, there is little evidence of the benefits of adding inspiratory training into aerobic regimens for breast cancer survivors who have undergone surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory physiotherapy is a set of techniques intended to prevent, treat, and stabilize cardiorespiratory disorders. 13 It is a helpful approach to preserving and enhancing functional capacity, quality of life, and post-treatment sequelae following breast cancer care. 14 , 15 However, there is little evidence of the benefits of adding inspiratory training into aerobic regimens for breast cancer survivors who have undergone surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it enhances the vital capacity and tidal volume of the lungs. 13 Most physical therapy interventions during and after COVID-19 focused on respiratory and general fitness rehabilitation in severely infected elderly individuals rather than balance and endurance training, as reported in the following studies: Mayer et al demonstrated an 8-week program of aerobic exercise, strengthening exercises, diaphragmatic breathing techniques, and mindfulness training for the post-COVID-19 case and assessed the patient's cognitive and emotional state. 14 Cevei et al conducted robotic gait training, occupational therapy, and messages on six elderly individuals post-COVID-19, evaluating their activity and participation by the Barthel index and functional independence measure.…”
Section: Introductionmentioning
confidence: 99%
“…17 A 10-week program using instrumental Pilates exercises with slow and controlled breathing exercises significantly improved heart rate variability (HRV) and respiratory parameters. 13 So, the most important feature that distinguishes this study from other research is that it aimed to treat mild-to-moderately recovered infected cases in younger adults using Pilates exercises to improve core muscle endurance and balance.…”
Section: Introductionmentioning
confidence: 99%